Interpretation of soil carbon and nitrogen dynamics in agricultural and afforested soils - Gregorich, E. G., author; Paustian, K., author; Six, J., author; Morris, S. J., author; Paul, Eldor A., author; Soil Science Society of America, publisher (Colorado State University. Libraries, 2003)
Interpretation of soil organic C (SOC) dynamics depends heavily on analytical methods and management systems studied. Comparison of data from long-term corn (Zea mays)-plot soils in Eastern North America showed mean residence times (MRTs) of SOC determined by 14C dating were 176 times those measured with 13C abundance following a 30-yr replacement of C3 by C4 plants on the same soils. However, MRTs of the two methods were related (r 2 = 0.71). Field 13C MRTs of SOC were also related (R 2 = 0.55 to 0.85) to those measured by 13CO2 evolution and curve fitting during laboratory incubation. The strong relations, but different MRTs, were interpreted to mean that the three methods sampled different parts of a SOC continuum. The SOC of all parts of this continuum must be affected by the same controls on SOC dynamics for this to occur. Methods for site selection, plant biomass, soil sampling and analysis were tested on agricultural, afforested-agriculture, and native forest sites to determine the controls on SOC dynamics. Soil-C changes after afforestation were −0.07 to 0.55 Mg C ha−1 yr−1 on deciduous sites and −0.85 to 0.58 Mg C ha−1 yr−1 under conifers. Soil N changes under afforestation ranged from −0.1 to 0.025 Mg N ha−1 yr−1 Ecosystem N accumulation was −0.09 to 0.08 Mg N ha−1 yr−1 Soil C and N sequestration but not plant biomass were related to soil Ca, Mg, and K contents. Comparative, independent assays of long-term plots provides information for concept testing and the confidence necessary for decision-makers determining C-cycle policies.
Keywords: soil fertility; ecosystem; global C cycle; SOM